Editorial: Special Issue on Unobtrusive Physiological Measurement Methods for Affective Applications - Pavlidis, Ioannis T.; Chaspari, Theodora; McDuff, Daniel (IEEE transactions on affective computing, 2023)
In The formative years of Affective Computing [1], from the late 1990s and into the early 2000s, a significant fraction of research attention was focused on the development of methods for unobtrusive physiological measurement . It quickly became obvious that wiring people with electrodes and strapping cumbersome hardware to their bodies was not only restricting the types of experiments that could be performed but also was not conducive to unbiased observations. For instance, subjects with fingers wrapped with electrodermal activity (EDA) and photoplethysmography (PPG) sensors could hardly type, drive or sleep comfortably. Hence, there was a need for more elegant and scalable physiological measurement methods [2].